APPLYING GAMIFICATION PRINCIPLES THROUGH THE DESIGN THINKING FRAMEWORK FOR DEVELOPING A MIXED REALITY EDUCATIONAL GAME IN NUMERACY LEARNING - Gumulya, Devanny; Suhanto, Yosefin (Universitas Telkom, 2023)
Numeracy is one of the most crucial literacy skills to develop at a young age. These skills are taught in the classroom through mathematics. According to several studies from the Programme for International Student Assessment (PISA), students' mathematical abilities in Indonesia remain low when compared to other literacy skills. This subject is often perceived as challenging and tedious. Furthermore, the concept of teaching numeracy skills cannot be approached abstractly initially, especially for children who require tangible objects for manipulation. The research employed a design thinking approach, encompassing diverse methodssuch as observation, interviews, questionnaires, literature review, direct observations involving children, and problem analysis. This project aims to create educational media infused with gamification elements such as points, badges, levels, and leaderboards. The final product of this design project is an educational toy named “LIGI” seamlessly integrated with a mobile app, referred to as